Disclosure of CSR and ESG Information in Sustainability Accounting Reporting of Public Companies in Indonesia: A Literature Review - Christine Dewi Nainggolan; Linda Lidyawati; Agus Sriyanto; Edison Sihombing; Liper Siregar (Journal of Innovative and Creativity, 2026)
This study reviews previous research on the disclosure of Corporate Social Responsibility (CSR) and Environmental, Social, and Governance (ESG) information in sustainability accounting reports of public companies in Indonesia. The main purpose of this paper is to summarize key discussions in the literature, identify commonly used theories and research methods, and highlight existing research gaps related to CSR and ESG disclosure practices. Materials and Methods. This study employs a literature review approach by collecting academic articles from national and international journals. The reviewed studies were published in reputable journals indexed in Scopus, Web of Science, and SINTA within the last ten years. Articles were selected based on their relevance to CSR disclosure, ESG disclosure, sustainability accounting, and public companies in Indonesia. The selected literature was systematically analyzed and classified based on research topics, theoretical frameworks, research methods, and key findings to identify overall patterns and research trends. Results. The review indicates a significant increase in CSR and ESG disclosure research in Indonesia over the past decade. Most studies apply legitimacy theory, stakeholder theory, and agency theory as the main theoretical foundations to explain corporate disclosure behavior. Quantitative approaches, particularly content analysis combined with regression or panel data analysis, dominate the research methods, while qualitative and mixed-method studies remain limited. Empirical findings generally suggest that CSR and ESG disclosure are positively associated with firm value, financial performance, and investor responses, although the quality and consistency of disclosures vary widely across companies and industries. Regulatory developments, such as mandatory sustainability reporting requirements, have encouraged broader disclosure practices; however, disclosure quality and standardization remain ongoing challenges. Conclusion. This review highlights several research gaps, including the limited use of integrated theoretical perspectives, insufficient attention to disclosure quality and assurance, and the lack of longitudinal and comparative studies. Future research is encouraged to explore the effectiveness of ESG disclosure, its real impact on corporate sustainability performance, and the role of institutional and regulatory factors in improving sustainability reporting practices in Indonesia.